The Innovation Optimism Paradox in Japan - Thomas, Merly (2013)
This report sought to better understand drivers and deterrents to innovation optimism both on a global scale and more specifically within Japanese firms. It utilized the framework established by the 2012 General Electric Innovation Barometer Survey alongside elements from the OECD-National Innovation Systems framework.Telephone interviews of 2,800 business executives in 22 markets operating across four global markets were conducted in order to gauge several perceptions surrounding innovation with relation to optimism, the innovation environment, models of Innovation and home country reputation. Global findings showed that firms were enthusiastic about the prospects of innovation and believed that innovation is relevant to drive firms seeking to reevaluate their corporate strategy. It is also relevant for economies that are looking to strengthen their competitive advantage in the global marketplace. The report is divided into results and discussion surrounding global perspectives and more specifically from a sample of 100 Japanese business executives. The data specific to the Japanese sample indicates that although Japan was voted as one of the three countries with the best innovation reputation by other markets, there is a paradox when looking at the less than optimistic responses from Japanese business leaders. This prompted for further exploration that highlights some of the key reasons why Japan’s business executives express this sentiment. It concluded that Japanese firms have a wealth of potential but need to adopt new strategies to keep up with the pace of innovation around the globe.